SHARPIN S146 phosphorylation mediates ARP2/3 interaction, cancer cell invasion and metastasis - Butt Umar; Khan Meraj H; Pouwels Jeroen; Westermarck Jukka (Company of Biologists, 2022)
SHARPIN is involved in several cellular processes and promotes cancer progression. However, how the choice between different functions of SHARPIN is post-translationally regulated is unclear. Here, we characterized SHARPIN phosphorylation by mass spectrometry and in vitro kinase assay. Focusing on S131 and S146, we demonstrate that they have a role in SHARPIN-ARP2/3 complex interaction, but play no role in integrin inhibition or LUBAC activation. Consistent with its novel role in ARP2/3 regulation, S146 phosphorylation of SHARPIN promoted lamellipodia formation. We also demonstrate that SHARPIN S146 phosphorylation-mediated ARP2/3 interaction is sensitive to inhibition of ERK1/2 or reactivation of protein phosphatase 2A (PP2A). Notably, CRISPR/Cas9-mediated knockout of SHARPIN abrogated three-dimensional (3D) invasion of several cancer cell lines. The 3D invasion of cancer cells was rescued by overexpression of the wild-type SHARPIN, but not by SHARPIN S146A mutant. Finally, we demonstrate that inhibition of phosphorylation at S146 significantly reduces in vivo metastasis in a zebrafish model. Collectively, these results map SHARPIN phosphorylation sites and identify S146 as a novel phosphorylation switch defining ARP2/3 interaction and cancer cell invasion. This article has an associated First Person interview with the first author of the paper.